Integrated Multidisciplinary Brain Metastasis Care Reduces Patient Visits and Shortens Time to Adjuvant Irradiation. Issue 11 (29th November 2022) - Moss, Nelson S.; El Ahmadieh, Tarek Y.; Brown, Samantha; Chen, Justin; Imber, Brandon S.; Pike, Luke; Reiner, Anne S.; Panageas, Katherine S.; Brennan, Cameron; Tabar, Viviane; Beal, Kathryn
Abstract : PURPOSE: Timely surgical cavity stereotactic radiosurgery (SRS) is an important adjuvant to brain metastasis resection, with earlier treatment associated with less frequent recurrence. The logistical complexity of treatment organization, however, has resulted in suboptimal start times postsurgically. We implemented a process improvement approach to reduce the time from surgery to adjuvant irradiation of resected brain metastases. METHODS: A multidisciplinary working group used process mapping to identify opportunities to reduce visits and shorten treatment times. The care delivery process was modified to streamline perioperative SRS preparation with (1) early patient identification, (2) preoperative intrateam communication, and (3) consolidation of required steps. Plan-Do-Study-Act cycles were used for process improvement. The surgery-to-SRS initiation time interval was the primary outcome. Secondary outcomes included the number of associated patient encounters. RESULTS: After implementation, the median (interquartile range) interval from surgery to SRS was reduced 48% from 27 (21-34) to 14 days (13-17; P < .001). The rate of surgical cavity SRS within 30 days increased from 64% (n = 63 of 98) to 97% (n = 60 of 62; P < .001). The median (interquartile range) number of CNS-associated encounters between resection and SRS decreased from 5 (4-6) to 4 (3-5; P < .001). The proportion of patients who had > 1 magnetic resonance imaging/computed tomography between surgery and SRS decreased from 45% (44 of 98) to 13% (8 of 62; P < .001). The time from surgery to systemic therapy resumption/initiation among patients treated within 90 days postoperatively decreased from 35 (24-48) to 32 days (23-40; P = .074). There were no wound complications in either group. CONCLUSION: Adjuvant SRS latency and treatment-associated encounters were significantly reduced after care-coordination implementation. This approach reduces patient and health care system burden and can be applied to other scenarios where early postoperative SRS administration is critical.